ANALISIS PUTUSAN HAKIM DI LUAR PASAL DAKWAAN PENUNTUT UMUM DALAM TINDAK PIDANA NARKOTIKA - Rafael, Tontji Christian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
This research aims to find out and analyze what the judge considers in making a criminal decision outside the articles of the public prosecutor's indictment for narcotics crimes? This research uses normative or doctrinal legal research methods which focus on the law approach, concept approach and case approach. In the research, it was found that the judge's consideration in handing down a decision beyond the public prosecutor's indictment in a narcotics crime was that the public prosecutor in determining the articles of indictment was based only on the conditions when the defendant was arrested. The public prosecutor did not consider the purpose and amount of the purchase of narcotics by the defendant before establishing the indictment. Applicability of Jurisprudence Number: 1671 K/pid/1996 which rendered a decision outside the indictment of the public prosecutor. The advice given by the author is that it is hoped that judges in deciding cases will always maintain the independence of the judiciary which has been mandated by the constitution and law and always be based on the law and everything proven in the trial by being active in finding the law and creating decisions that reflect legal values, namely justice, certainty and legal benefits for every justice seeker.